Delivery And Development Of Msmes For The Community In Sukarame Village During The Covid-19 Pandemic - Dian Sugito; Annisa Desta Pusmawati; Febrianti Dewi; Nanda Purnamasari Senoputri; Niar Putri Gusdinar; Nita Nurpadila (Indonesian Journal of Community Empowerment (IJCE), 2022)
Abstract Covid-19 affects various aspects of one of them is the economy. Therefore, to increase the economic income of the community developed MSMEs. This service aims to develop businesses that can improve the economy of the community in the pandemic era, through methods of mentoring the community in developing creative, innovative and modern businesses during the Covid-19 pandemic. This devotion is focused on food MSMEs in Kp. Ciperang and Kp. Segleng Sukarame Village, Leles District, Garut district which is one of the businesses by utilizing abundant raw materials such as cassava. Abstrak Covid-19 berpengaruh terhadap berbagai aspek salah satunya adalah perekonomian. Oleh karena itu untuk meningkatkan pendapatan ekonomi masyarakat dikembangkanlah UMKM. Pengabdian ini bertujuan untuk mengembangkan usaha yang dapat meningkatkan perekonomian masyarakat di era pandemi, melalui metode pendampingan terhadap masyarakat dalam mengembangkan usaha yang kreatif, inovatif serta modern dimasa pandemic Covid-19. Pengabdian ini difokuskan pada UMKM makanan di Kp. Ciperang dan Kp. Segleng Desa Sukarame Kecamatan Leles kabupaten Garut yang merupakan salah satu usaha dengan memanfaatkan bahan baku yang melimpah yaitu singkong